The social as object of museology (Cadernos de Sociomuseologia, 2014)
The notion of social started to take shape as an object of study of museology from the 70 years of the twentieth century. The social, political, cultural, educational and economic transformations that have been unleashed throughout the second half of the twentieth century were engines for the changes in the theoretical-methodological field of Museology. The New Museology Movement gained strength in almost all of the Western world, proposing and carrying out actions and interactions that aimed to transform the museum-Temple to the consolidation of the Museum-Forum (Cameron, 1971), calling on social subjects to withstand determinism history of heroes and glorious past and actively intervene in favor of a social and culturally transformative present.Keywords: New Museology; Museum; Heritage; Identity; Comunity, Nova Museologia, museu, património, identidade, comunidade